Peptide Toxins as Biothreats and the Potential for AI Systems to Enhance Biosecurity - Lee, Ying-Chiang J.; Cowan, Alexis; Tankard, Amari (Frontiers in Bioengineering and Biotechnology, 2022)
Biological weapons have been used for thousands of years, but recent advances in synthesis technologies have made peptide and protein toxin production more accessible and pose a threat to biosecurity worldwide. Natural toxins such as conotoxins, certain hemolytic compounds, and enterotoxins are peptide agents that can be synthesized in an environment with weak biosecurity measures and rudimentarily weaponized for limited use against smaller targets for lethal or nonlethal effects. Technological advances are changing the threat landscape around biological weapons and potentially facilitating a shift from state sponsored to more micro-level threats stemming from terror cells, insider threats, and lone wolf attacks. Here, we present the reader with an overview of the threat of peptide and protein toxins, provide examples of potent peptide toxins, and introduce capabilities of a proposed biosecurity program utilizing artificial intelligence that unifies commercial nucleotide and peptide synthesis vendors.